Analisis Penyebab Bank Runs (Studi Kasus Svb Silicon Valley Bank) - Joseph Silaban; Desi Syahrani; Selvi Indriani; Hasyim . (Peneliti.net, 2023)
The purpose of this article is to analyze the factors that influenced the downfall of the USbased Silicon Valley Bank (SVB). This research is a qualitative research using secondary data as research supporting data. Data collection techniques in this study used document study techniques by obtaining data from websites, articles, books, and other literatures. Liquidity risk management failure, Interest rates of central bank (Fed), as well as portofolio investment missalocation drive the fall of SVB. Liquidity risk management plays an important role in the short and long term sustainability of bank. Therefore, there are efforts should be made to prevent various liquidity problems such as tightening lending, strenghtening coordination between central bank and commercial banks, as well as improving and evaluating the liquidity risk assessment system at related banks